Systematic review of measurement properties of patient reported outcome measures used in patients undergoing hip and knee arthroplasty - Harris, K; Dawson, J; Gibbons, E; Lim, C; Beard, D; Fitzpatrick, R; Price, A (Dove Medical Press, 2016)
Objectives To identify Patient-reported Outcome Measures (PROMs) which have been developed and/or used with patients undergoing hip or knee replacement surgery and to provide a short-list of the most promising generic and condition specific instruments. Methods A systematic review of the literature was performed to identify measures used in patients undergoing hip and knee replacement and extract and evaluate information on their methodological quality. Results 32 shortlisted measures were reviewed for the quality of their measurement properties. Based on the review criteria, the measures with most complete evidence to date are the Oxford Hip Score (OHS) (for patients undergoing hip replacement surgery), and the Oxford Knee Score (OKS), with OKS activity and participation questionnaire (OKS-APQ) (for patients undergoing knee replacement surgery). Conclusions A large number of these instruments lack essential evidence of their measurement properties (e.g. validity, reliability, responsiveness) in specific populations of patients. Further research is required on almost all of the identified measures. The best performing condition specific PROMs were the OKS, OHS, and WOMAC. The best performing generic measure was the SF-12. Researchers can use the information presented in this review to inform further psychometric studies of the reviewed measures.